Preparation and characterization of TiO2/HZSM-11 zeolite forphotodegradation of dichlorvos in aqueous solution - Gómez, Silvina del Valle (2013)
The TiO2/HZSM-11 materials were synthesized using titanium isopropoxide as a TiO2precursor andHZSM-11 a medium pore size zeolite with high thermal and chemical resistance as support. The amountof titanium isopropoxide was varied in order to obtain TiO2concentrations of 3, 10, 20, 30 and 50 wt%in the final material. They were characterized by a series of complementary techniques: X-ray diffrac-tion (XRD), ultraviolet?visible diffuse reflectance spectroscopy (DRS), transmittance Fourier transforminfrared spectroscopy (FTIR) and scanning electron microscopy (SEM). The surface area of the TiO2/HZSM-11 samples decreased with the increment of TiO2loading. As result of the increment of the calcinationtemperature from 450 to 800◦C an increase in the size of the anatase crystals was observed. However,the X-ray diffraction patterns of the solids only presented the characteristic peaks of the anatase phase.The catalytic activity of the materials in the photodegradation of Dichlorvos (DDVP) depended on theTiO2amount the thermal treatment temperature. The sample containing 30% TiO2calcined at 450◦Cshowed the best catalytic performance and it can be reused without noticeable activity loss during atleast four cycles. The catalytic performance was similar to that of the P25 Degussa used as a referencebut its separation, recovery and reuse was easier.